The Effect of Store lmage and Store Atmosphere on ImpuIse Buying in Metro Supermarket Consumers (Study on Metro Supermarket Consumers) - Suliandri, Fransiska Ayu; Safrin, Feby Aulia (Formosa Journal of Applied Sciences, 2024)
The era of globalization and ongoing technological advances makes competition in the business world increasingly fierce. The purpose of this research is to determine the influence of store image and store atmosphere on impulses buying. The research method uses quantitative methods with an associative approach. The sample was determined using a purposive sampling method, so that 100 respondents were determined to answer questions from the questionnaire distributed as a primary data source. Meanwhile, secondary data is done through literature study. Data analysis techniques use instrument testing, validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using SPSS. The results of the research are that store image and store atmosphere have a positive and significant influence on impulses buying.